Neno Boha: Local Wisdom of the Dawan Community tn Postpartum Mothers in Binaus Village - Tatie Justicia Nenohaifeto; Marni Marni (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Health promlems in Indonesia include high maternal and infant mortality rates. The causes are varied, including economic factors, access to health facilities, and community beliefs and traditions. In Binaus Village, there is a Neno Boha tradition for caring for mothers after giving birth, which involves roasting, hot water compresses (tatobi), abstinence, and consuming potions. This research aims to understand the implementation of the Neno Boha tradition and its impact on maternal and infant health Methods: This research uses a qualitative method with an ethnographic approach to postpartum mothers who follow the Neno Boha tradition. Data was collected through in-depth interviews and participant observation, then analyzed thematically by coding the interview transcripts to produce sub-themes and themes. The results are presented in descriptive text. Results: Data analysis shows that the Dawan tribe women in Binaus Village still carry out the Neno Boha tradition because of this belief passed down from generation to generation. They believe that this tradition helps restore health and heal post-natal wounds. Mothers continue to observe Neno Boha even after giving birth in a health facility and taking medication, because they believe this tradition prevents various long-term illnesses. The practice of roasting and tatobi is thought to help expel dirty blood, making the mother feel healthier. However, for the sake of the baby's health, the practice of roasting is now done only with hot coals and in the main house Conclusion: Traditional care for mothers after giving birth is still carried out by the Dawan tribe community in Binaus Village. The mother feels that the Neno Boha tradition needs to be carried out in addition to medical treatment, by avoiding things that could harm the mother and baby.